Relationship Between Diaper Usage and Toddler Readiness for Toilet Training Readiness - Amir, Rahmi; Karim, Chadija (KnE Social Sciences, 2023)
This study aimed to determine whether the use of diapers influences toddlers’ readiness for toilet training. This quantitative-comparative research used a case-control design. Twenty-four children were in the study group and twenty-four children were in the control group. They were selected through purposive sampling. The instrument used was a questionnaire. Data analysis was done through Bivariate analysis with the Chi-Square and Odd Ratio statistical test. The results found a significant relationship between the use of diapers and toddlers’ readiness for toilet training readiness. The OR showed that toddlers still using diapers were 26 times more at risk of being unprepared for toilet training than toddlers not using diapers. Keywords: Diapers, Toilet Training, Toddler